Talent Management Strategies in the Gig Economy: Challenges and Opportunities for Modern Organizations - Mulyadi, Mulyadi; Amang, Andi; Permata Sari, Dewi; Musa, Sulaiman (International Journal of Economics Development Research (IJEDR), 2025)
This study explores the challenges and opportunities in talent management strategies for the gig economy, where short-term, flexible work arrangements are increasingly prominent. The research employs a qualitative approach, utilizing an extensive literature review of journal articles, to examine key themes related to managing gig workers. Findings reveal that while the gig economy offers significant benefits to organizations—such as cost efficiency, access to diverse expertise, and operational flexibility—it also presents challenges, including high turnover rates, difficulties in worker retention, and the integration of gig workers into organizational culture. The study emphasizes the need for adaptive talent management strategies tailored to the unique demands of gig work, such as flexible onboarding processes, project-based engagements, competitive compensation, and opportunities for skill development. Practical recommendations include fostering engagement through transparent communication and the use of digital collaboration tools to enhance remote worker cohesion. Given the study’s reliance on literature review, future research is encouraged to incorporate empirical data, such as interviews or surveys with gig workers and employers, to further validate and enrich the findings. This study contributes to the growing body of knowledge on talent management within the gig economy and provides actionable insights for organizations seeking to effectively engage and manage gig talent.